Determination of Vigilance-bound Learning Style based on EEG - Nazre, Abdul Rashid; Mohd Nasir, Taib, Prof. Dr.; Sahrim, Lias; Norizam, Sulaiman; Zunairah, Hj Murat; Ros Shilawani, S. Abdul Kadir (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/